\documentclass{article} \usepackage{hyperref} \usepackage[scr]{rsfso} \def\rload{R_{\rm load}} \date{} \begin{document} \title{Project Executive Summary} \author{Holden Rohrer and Nithya Jayakumar} \maketitle \section{Matrix Representation and Homogeneous Solution} To determine the relevant properties of the linear system, matrix form is useful (this form was chosen to reduce fractions' usage): \def\x{{\bf x}} $$\x' = {1\over R_1C_1C_2\rload} \pmatrix{0&-C_2\rload &0 \cr 0&-C_2(R_1+\rload)&C_1R_1\cr 0&C_2R_1 &-C_1R_1} \x + {1\over R_1} \pmatrix{\omega\cos(\omega t)\cr \omega\cos(\omega t)\cr 0} .$$ \section{Application of Laplace Transformation} We can apply the Laplace Transformation in order to solve this system of differential equations. We have the three equations for $x'$, $y'$, and $z'$, and we can take the Laplace Transform of each of these equations" $$\mathscr{L}\{x' = \frac{-y}{C_1R_1} + \frac{\omega\cos(\omega t)}{R_1}\} \Rightarrow sX(s) - x(0) = \frac{Y(s)}{C_1R_1} + \frac{\omega s}{R_1(s^2 + \omega^2)}$$ $$\mathscr{L}\{y' = y\frac{-R_1 - \rload}{R_1C_1\rload} + \frac{z}{C_2\rload} + \frac{\omega\cos(\omega t)}{R_1} \} \Rightarrow sY(s) - y(0) = Y(s)(\frac{-R_1-\rload}{R_1C_1\rload}) + \frac{Z(s)}{C_2\rload} + \frac{\omega s}{R_1(s^2 + \omega^2)}$$ $$\mathscr{L}\{z' = \frac{y}{C_1\rload} - \frac{z}{C_2\rload} \} \Rightarrow sZ(s) - z(0) = \frac{Y(s)}{C_1\rload} - \frac{Z(s)}{C_2\rload}$$ The last two equations we get can be used to solve for $Z(s)$, which we find to be $$Z(s) = \frac{\omega s(C_1C_2\rload^2)}{(s^2 + \omega^2)(s^2 + s(C_1R_1\rload + R_1C_2\rload + \rload^2C_2) + \rload)}$$ We can now find the partial fraction decomposition of this: $$Z(s) = \frac{\omega s(C_1C_2\rload^2)}{(s^2 + \omega^2)(s^2 + s(C_1R_1\rload + R_1C_2\rload + \rload^2C_2) + \rload)} = $$ $$\frac{As + B}{s^2 + \omega^2} + \frac{Cs + D}{(s^2 + \omega^2)(s^2 + s(C_1R_1\rload + R_1C_2\rload + \rload^2C_2) + \rload)} = \omega sC_1C_2\rload^2$$ To simplify notation, let $b = (s^2 + \omega^2)(s^2 + s(C_1R_1\rload + R_1C_2\rload + \rload^2C_2) + \rload)$ We find that $$A = \frac{C_1C_2\rload^2\omega (\rload - \omega^2)}{b^2\omega^2 + \rload^2 - 2\rload - 2\rload\omega^2 + \omega^2}$$ $$B = \frac{bC_1C_2\rload^2\omega^3}{b^2\omega^2 + \rload^2 - 2\rload\omega^2 + \omega^4}$$ $$C = \frac{-C_1C_2\rload^2\omega(\rload - \omega^2)}{b^2\omega^2 + \rload^2 - 2\rload\omega^2 + \omega^4}$$ \end{document}